Finestre e finestrini: sguardi plurimi e incrociati sul “pays-temps” di Louis-Philippe Dalembert (Altre Modernità, 2015)
The article focuses on the presence and the absence of windows, and specifically windows with shutters, car windows and rear-view mirrors in the novels by Haitian writer Louis-Philippe Dalembert. In his work, we can identify three tendencies. First of all, windows with shutters allow the passage from childhood to adulthood. Secondly, the absence of openings projects the character in heterotopias, which cause a language breakdown. Thirdly, the use of literary windows is linked with vagabondage and pays-temps. An image of the landscape is selected through a frame and we have the perception of a fragmentary vision. According to Dalembert, this world vision becomes a narrative element and a creative technique. This partial image which emerges from the symbolic space of the window allows us to talk about the childhood of the narrator from different perspectives: we can identify a geographical and temporal landscape (pays-temps) thanks to a reflection on the surface of the window and the possibility of remembering and imaging the past. Fiction is able to complete omissions, gaps, lapses.